Development And Application Of Game-Based Learning Software Combining Role-Playing With Problem-Solving Strategies - Chang, Shu-Ping; Hou, Huei-Tse; Chang, Rong-Chi (Advances in Social Sciences Research Journal, 2015)
With the development of educational technology, game-based learning has been gradually applied to teaching practice. This study is divided into two phases. In phase 1, systematic development process was used to develop a simulation e-learning game combining role-playing with problem-solving strategies called “Instructional Design Guidelines – Gem Quest.” This game aims to enable learners who intend to act as “game-based learning instructional designers” in e-learning industry to apply the instructional design knowledge, procedures, and project management skill they have learned, experience the practical work contexts in workplaces, and further use problem-solving strategies to complete tasks in the game before they engage in such work. This game is divided into 5 stages: raw materials, structure, storyboard, product, and online. Learners played the role as the game-based learning designers in the contexts, and had to interact and communicate with the members of various projects in the contexts to implement the projects. The conditions for stage completion and feedback mechanism of the game were designed according to the actual workplace status. Upon completion of this software, Phase 2 is an empirical study was conducted during course instruction to investigate learners’ technology acceptance and learning effectiveness of application of this game. The participants were a total of 51 sophomores of Department of Multimedia Design in a certain university in the northern Taiwan. The research results showed that, learners’ technology acceptance of this game is above the median, and there is a significant difference in their stage completion and posttest scores.